Citizen science interactions with official geospatial information; Case studies from Mexico - Jacquin, Céline; Merodio Gómez, Paloma; Arriaga, Vivian; Santiago, Andrea (Frontiers in Environmental Science, 2023)
This paper presents an overview of the integration of participatory processes in the production of official data. Through a series of interviews with strategic stakeholders we identified the key elements to institutionalize citizen science in the production of geospatial information. This article discusses practical contexts of uses of data produced or complemented by citizens in Mexico. We analyze institutional processes that facilitates or make difficult the integration into official mechanisms for generating more accurate cartographic information in various institutions, focusing on its possible adoption, in particular by the National Institute of Statistics and Geography (INEGI) of Mexico. Resources, data integration models, workflows, and an organizational structure are needed to benefit from citizen science. We find that the adoption of citizen science within an organization is subject to a well-defined and structured interest driven by leadership and implemented collectively. This presents a paradigm shift in obtaining information, citizen science as official data through concrete and functional information products will allow end users to benefit from timely and accurate data. The purpose of this article is then to generate organizational knowledge on how to use citizen science in public institutions, with a long-term perspective, to mediate the lack of current and accurate spatial data and participate in social innovation.